The study of qualitative cases: a practica experience - Saavedra Guajardo, Eugenio (2009)
The objetive of the present article is to develop the main concepts of the use of the Case Study Qualitative Method in research. At first, the sstudy method is defined, differentiating the “Unique cases” from the advantages and disadvantages of this investigation fromat are mentioned. The contents of those interviews are all introduced in the category of meaning